2021
DOI: 10.3389/fneur.2021.746486
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation as a Key Mechanism for the Protective Effects of Remote Ischemic Conditioning After Stroke

Abstract: Remote ischemic conditioning (RIC), which involves a series of short cycles of ischemia in an organ remote to the brain (typically the limbs), has been shown to protect the ischemic penumbra after stroke and reduce ischemia/reperfusion (IR) injury. Although the exact mechanism by which this protective signal is transferred from the remote site to the brain remains unclear, preclinical studies suggest that the mechanisms of RIC involve a combination of circulating humoral factors and neuronal signals. An improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 213 publications
(308 reference statements)
0
8
0
Order By: Relevance
“…Among the multiple candidates that have been proposed as putative mediators of the protective effects of RIC, the extracellular vesicles (small endogenous particles that contain cytokines, chemokines, genetic material, and many more biological substrates) can facilitate the transfer of protective effects of RIC through the flow stream, and allow them to interconnect distant cells, tissues, or organs and affect the target cells’ transcriptional profiles and likely their function and phenotype. 16 The above stimulus can subsequently deliver either proinflammatory or anti-inflammatory factors, and modulate the immune response. In addition, a number of mainly preclinical studies have demonstrated that the presence of certain comorbidities (such as age, metabolic syndrome, and hypertension) and comedications (such as statin) may interfere with the cardioprotective and neuroprotective effect of conditioning protocols such as RIC, and this should also be taken into consideration when interpreting the results from different trials.…”
Section: Exploring Specific Biomarkers and Optimal Protocolsmentioning
confidence: 99%
“…Among the multiple candidates that have been proposed as putative mediators of the protective effects of RIC, the extracellular vesicles (small endogenous particles that contain cytokines, chemokines, genetic material, and many more biological substrates) can facilitate the transfer of protective effects of RIC through the flow stream, and allow them to interconnect distant cells, tissues, or organs and affect the target cells’ transcriptional profiles and likely their function and phenotype. 16 The above stimulus can subsequently deliver either proinflammatory or anti-inflammatory factors, and modulate the immune response. In addition, a number of mainly preclinical studies have demonstrated that the presence of certain comorbidities (such as age, metabolic syndrome, and hypertension) and comedications (such as statin) may interfere with the cardioprotective and neuroprotective effect of conditioning protocols such as RIC, and this should also be taken into consideration when interpreting the results from different trials.…”
Section: Exploring Specific Biomarkers and Optimal Protocolsmentioning
confidence: 99%
“…Further studies showed transient cyclical ischemia-reperfusion to a limb muscles or in a remote organ can offer protection not only against heart, but also other organs including brain, liver, and kidneys [ 7 10 ]. The mechanism of action of remote ischemic conditioning is through humoral, neural and immunomodulatory pathways [ 11 ]. Early-phase 2 and a few phase 3 human clinical trials on RIC in ischemic stroke have been promising so far [ 12 15 ].…”
Section: Background and Rationalementioning
confidence: 99%
“…Tissue injuries caused by ischemia or ischemia–reperfusion (IR) can be separated into two phases: the first is caused directly by hypoxia and hypoglycemia during blood vessel occlusion, and the second is attributable to the ensuing inflammation [ 119 , 120 ]. DAMPs released from injured cells in the first phase play a major part in triggering and intensifying inflammation in the vicinity of ischemic loci [ 120 ].…”
Section: Association Of Cxhc With Pathogenesis Of Inflammatory Diseasesmentioning
confidence: 99%